Cross-checking SMBH mass estimates in NGC 6958 – I. Stellar dynamics from adaptive optics-assisted MUSE observations. Issue 4 (10th November 2021) - Thater, Sabine; Krajnović, Davor; Weilbacher, Peter M; Nguyen, Dieu D; Bureau, Martin; Cappellari, Michele; Davis, Timothy A; Iguchi, Satoru; McDermid, Richard; Onishi, Kyoko; Sarzi, Marc; van de Ven, Glenn
ABSTRACT: Supermassive black hole masses ( M BH ) can dynamically be estimated with various methods and using different kinematic tracers. Different methods have only been cross-checked for a small number of galaxies and often show discrepancies. To understand these discrepancies, detailed cross-comparisons of additional galaxies are needed. We present the first part of our cross-comparison between stellar- and gas-based M BH estimates in the nearby fast-rotating early-type galaxy NGC 6958. The measurements presented here are based on ground-layer adaptive optics-assisted Multi-Unit Spectroscopic Explorer (MUSE) science verification data at around 0${_{.}^{′′}}$ 6 spatial resolution. The spatial resolution is a key ingredient for the measurement and we provide a Gaussian parametrization of the adaptive optics-assisted point spread function for various wavelengths. From the MUSE data, we extracted the stellar kinematics and constructed dynamical models. Using an axisymmetric Schwarzschild technique, we measured an M BH of $(3.6^{+2.7}_{-2.4}) × 10^8\, $ M⊙ at 3σ significance taking kinematical and dynamical systematics (e.g. radially varying mass-to-light ratio) into account. We also added a dark halo, but our data do not allow us to constrain the dark matter fraction. Adding dark matter with an abundance matching prior results in a 25 per cent more massive black hole. Jeans anisotropic models return M BH of $(4.6^{+2.5}_{-2.7}) × 10^8$ and $(8.6^{+0.8}_{-0.8}) × 10^8\, M_{\odot }$ at 3σ confidence for spherical and cylindrical alignments of the velocity ellipsoid, respectively. In a follow-up study, we will compare the stellar-based M BH with those from cold and warm gas tracers, which will provide additional constraints for the M BH for NGC 6958, and insights into assumptions that lead to potential systematic uncertainty.